2019
DOI: 10.1097/md.0000000000015872
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals novel gene expression signatures of trastuzumab treatment in HER2+ breast cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…These results indicated that the DEG selected for this data set not only represents the trastuzumab treatment but also, the differences between the gene expression profile from HER2+ patients. In addition, these results are in agreement with previously published results (Wang et al, 2019). The energy landscape built for HER2+ treated and nontreated samples is shown in Figure 8A.…”
Section: Simulation Of Trastuzumab Treatment Effectsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that the DEG selected for this data set not only represents the trastuzumab treatment but also, the differences between the gene expression profile from HER2+ patients. In addition, these results are in agreement with previously published results (Wang et al, 2019). The energy landscape built for HER2+ treated and nontreated samples is shown in Figure 8A.…”
Section: Simulation Of Trastuzumab Treatment Effectsupporting
confidence: 92%
“…Stratification of patients may improve treatment outcomes through the identification of molecular targets common to a group of patients (He et al, 2019). For instance, trastuzumab is a monoclonal antibody, used as adjuvant treatment against breast and stomach cancers that overexpress the HER2 protein (Wang et al, 2019). Also, triple-negative breast cancer patients may present resistance to neoadjuvant chemotherapy due to pre-existing resistant cell phenotypes (Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of single-cell transcriptional profiles of individual cells at different treatment timepoints could lead to deeper insight into the evolution of cell states of both cancer cells and TME cells occurring during treatment. There is currently a paucity of single-cell transcriptome studies that sample metastatic solid malignancies and prior scR-NAseq studies of metastatic disease largely focused on individual treatment timepoints (Chung et al, 2017a;Darmanis et al, 2017;Lambrechts et al, 2018a;Patel et al, 2014a;Tirosh et al, 2016a;Wang et al, 2019;Zhang et al, 2019a). This is due, in part, to challenges associated with obtaining high-quality biopsies from metastatic tumors, instead of the larger tumor specimens that can be obtained from surgically resected earlier-stage disease.…”
Section: R a F Tmentioning
confidence: 99%
“…Among the differentially overexpressed genes at RD were genes associated with the alveolar cell signature, cell growth, differentiation, and cell motility (Supplemental Table 5). RD cancer cells overexpress surfactant genes (SFTPB/C/D and SFTA3) which are part of the alveolar cell signature ( Figure 3A, Supplemental Figure 3B) (Desai et al, 2014;Treutlein et al, 2014;Wang et al, 2018). Furthermore, RD cancer cells also overexpress the putative tumor suppressor DLC1, which is a member of the RhoGAP family of negative regulators of Rho GTPases and can be downregulated in NSCLC (Healy et al, 2008;Yuan et al, 2004).…”
Section: Longitudinal Scrnaseq Profiles Of Cancer Cells Change From Rmentioning
confidence: 99%
“…Trastuzumab is still the most prevalent treatment for human epidermal growth factor receptor 2 (HER2) positive breast cancer. However, cardiotoxicity and cardiomyopathy of trastuzumab limit its clinical utility [1,2]. Studies have shown that lack of HER2 in mouse heart causes dilated cardiac chambers and myocardial wall thinning and as a result development of cardiomyopathy [3,4].…”
Section: Introductionmentioning
confidence: 99%